Macro and microstructural characterisation of high Si cast steels – Study of microsegregation patterns. (4th March 2017) - Tenaglia, Nicolás E.; Boeri, Roberto E.; Basso, Alejandro D.; Massone, Juan M.
Abstract: In this study the as-cast macro and microstructures of medium C – high Si cast steels of three different levels of alloying are characterised. The application of a colour-etching reagent sensitive to Si segregation effectively revealed the solidification macrostructure, showing that the patterns of macrostructure and microsegregation are governed by the initial precipitation of δ-ferrite dendrites. A study of microsegregation carried out using advanced EDS techniques showed that, for the studied chemical compositions, Si, Mn, Cr, Ni, Mo and Al tend to concentrate at the last liquid to solidify. Accordingly, effective partition coefficients of values below unity were calculated for all alloying elements tested. It was verified that the minimum local Si contents measured on the steels investigated were greater than 1.7%, value above the minimum value (1.5%) necessary to obtain carbide-free bainite after austempering.